Gestão Educacional e Gerenciamento Estratégico: uma integração por meio da metodologia de Balanced Scorecard (BSC) aplicada à realidade de escola de Educação Básica - Carvalho, Mônica Timm de (Universidade do Vale do Rio dos Sinos, 2015)
The purpose of this study is to integrate Educational Management and Strategic Management, having the Elementary School at Colegio Israelita Brasileiro as its corpus of research. This project starts with the review of the current strategic formulation of this educational institution to build through the Balanced Scorecard (BSC) methodology, a description model and an organizational performance assessment that enables the management of continuous alignment of the School to the demands of its time. Exploratory and qualitative studies were conducted for the analysis of the strategic positioning of Colegio Israelita Brasileiro. The studies were based on data research, benchmarking procedures, focus groups interviews and semi-structured interviews with the school representatives. The information obtained from this step served as a subsidy for the construction of the School Strategic Map and the definition of performance indicators associated with each of its main objectives. As a result of the investigation, there is the indication of a review of the strategic positioning of Colegio Israelita Brasileiro. A new formulation was designed and described in strategic perspectives, objectives and performance indicators, as proposed by the Balanced Scorecard (BSC), to contribute to the school in their adoption process of strategic management practices to achieve the desired excellence.
Keywords: Gestão educacional; Gerenciamento estratégico; Estratégia; Indicadores de desempenho; Balanced scorecard (BSC); Educational management; Strategic management; Performance indicators; ACCNPQ::Ciências Humanas::Educação